2011
DOI: 10.1364/ol.36.003575
|View full text |Cite
|
Sign up to set email alerts
|

220 μJ monolithic single-frequency Q-switched fiber laser at 2 μmby using highly Tm-doped germanate fibers

Abstract: We report a unique all fiber-based single-frequency Q-switched laser in a monolithic master oscillator power amplifier configuration at ~1920 nm by using highly Tm-doped germanate fibers for the first time. The actively Q-switched fiber laser seed was achieved by using a piezo to press the fiber in the fiber Bragg grating cavity and modulate the fiber birefringence, enabling Q-switching with pulse width and repetition rate tunability. A single-mode polarization maintaining large core 25 μm highly Tm-doped germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…The all-fiber monolithic configuration, which has the unique advantages of robustness, compactness, and low maintenance, has been employed to generate narrow-linewidth nanosecond pulses in recent years. Shi et al [16] and Geng et al [17] have developed narrow-linewidth all-fiber actively Q-switched lasers using the method of piezo-induced birefringence. Fang et al [18] and Liu et al [1] have demonstrated narrow-linewidth pulses by employing a fiber pigtailed intensity modulator.…”
Section: Introductionmentioning
confidence: 99%
“…The all-fiber monolithic configuration, which has the unique advantages of robustness, compactness, and low maintenance, has been employed to generate narrow-linewidth nanosecond pulses in recent years. Shi et al [16] and Geng et al [17] have developed narrow-linewidth all-fiber actively Q-switched lasers using the method of piezo-induced birefringence. Fang et al [18] and Liu et al [1] have demonstrated narrow-linewidth pulses by employing a fiber pigtailed intensity modulator.…”
Section: Introductionmentioning
confidence: 99%
“…Then the PZT was clamped on the fiber between the splice and the HR FBG [13] to achieve the Q-switched operation. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the Q-switched all-fiber lasers based on the stressinduced birefringence have been investigated in 2 mm region [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Single .frequency .lasers near .2 µm, which play a significant role in many applications such as coherent LIDAR, coherent beam combining, nonlinear frequency conversion, medicine, atmospheric sensing and spectroscopy, have attracted intense interest and have been widely investigated [1][2][3][4][5][6][7][8][9][10][11][12] . In recent years, 2 µm single frequency fiber lasers have undergone rapid development [11][12][13][14][15][16][17][18][19][20][21][22] since fiber lasers have outstanding advantages including high efficiency, considerable compactness, convenience for thermal management, high beam quality and excellent stability.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, 2 µm single frequency fiber lasers have undergone rapid development [11][12][13][14][15][16][17][18][19][20][21][22] since fiber lasers have outstanding advantages including high efficiency, considerable compactness, convenience for thermal management, high beam quality and excellent stability. To realize single frequency fiber laser near 2 µm, distributed Bragg reflector (DBR) [15] and distributed-feedback (DFB) [12,19] techniques have been employed, the output power is limited and should be further amplified for practical applications.…”
mentioning
confidence: 99%